Comparison between tonsillotomy and tonsillectomy of young children 2 years post surgical followup - Faisal, Khandakar Ahmed; Mahmud, Khaled; Ahmed, Omar Aziz (Journal of Dhaka National Medical College & Hospital, 2022)
Objectives: To study the long-term effect of tonsillotomy and tonsillectomy in young children after two years in comparison to the results after six months. Method: Children, age 4-5 with Sleep Disordered Breathing (SDB) and tonsil hyperplasia, were randomized to TE (32) or TT (35). TT was performed by diathermy. An adenoidectomy with cold steel (Universal Dissection Method) was performed in the same session for 80% of cases. The patients were assessed prior to surgery, at six and 24 months postoperatively. Effects of surgery were evaluated clinically, through questionnaire (general health/snoring/ENT-infections), Quality of Life (QoL), survey of pediatric obstructive sleep apnea with OSA-18, and children's behavior with the Child Behavior Checklist. Results: After two years there was still no difference between the groups with respect to snoring and frequency or severity of upper airway infections. Both TT and TE had resulted in large improvement in short and long term QoL and behavior. Three TT-children and one TE child had been re-operated due to recurrence of obstructive problems, the TE-child and one of the TT-children with adenoidectomy and two of the TT-children with tonsillectomy. Three of the TT-children had tonsil tissue protruding slightly out of the tonsil pouch and twelve TE-children had small tonsil remnants within the tonsil pouches, but with no need for surgery. Conclusion: Younger children have a small risk of symptom-recurrence requiring re-surgery within two years after TT. For the majority, the positive effect on snoring, infections, behavior and quality of life remain and is similar to TE. J. Dhaka National Med. Coll. Hos. 2022; 28 (01): 20-26